Caffeinated energy drinks improve high-speed running in elite field hockey players - Del Coso, J.; Portillo, J.; Salinero, J. J.; Lara, B.; Abian-Vicen, J.; Areces. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The aim of this investigation was to determine the efficacy of a caffeine-containing energy drink to improve physical performance of elite field hockey players during a game. On 2 days separated by a week, 13 elite field hockey players (age and body mass = 23.2 ± 3.9 years and 76.1 ± 6.1 kg) ingested 3 mg of caffeine per kg of body mass in the form of an energy drink or the same drink without caffeine (placebo drink). After 60 min for caffeine absorption, participants played a simulated field hockey game (2 × 25 min). Individual running pace and instantaneous speed during the game were assessed using GPS devices. The total number of accelerations and decelerations was determined by accelerometry. Compared with the placebo drink, the caffeinated energy drink did not modify the total distance covered during the game (6,035 ± 451 m and 6,055 ± 499 m, respectively; p = .87), average heart rate (155 ± 13 beats per min and 158 ± 18 beats per min, respectively; p = .46), or the number of accelerations and decelerations (697 ± 285 and 618 ± 221, respectively; p = .15). However, the caffeinated energy drink reduced the distance covered at moderate-intensity running (793 ± 135 and 712 ± 116, respectively; p = .03) and increased the distance covered at high-intensity running (303 ± 67 m and 358 ± 117 m; p = .05) and sprinting (85 ± 41 m and 117 ± 55 m, respectively; p = .02). Elite field hockey players can benefit from ingesting caffeinated energy drinks because they increase the running distance covered at high-intensity running and sprinting. Increased running distance at high speed might represent a meaningful advantage for field hockey performance.